Kristliku kiriku ja (voorus)eetika panusest meditsiini ja tervisedenduse arengus - Remmel, Meego (Usuteaduslik Ajakiri, 2020)
The Contribution of Christian Church and (Virtue) Ethics to the Development of Medicine and Health Promotion COVID-19 crisis has challenged Estonian churches both in practical issues as well as in ethical reflection into a dialogue with nowadays medicine and health promotion. Learning from biblical background, historical experience of the church, and current discussions on Christian ethics, the author shows how churches in Estonia could particularly via ecumenical cooperation benefit more and relate better to medical development and future of health promotion by Christian virtue ethics approach.